A review on Design of Gene Therapy and Its Potential for Craniofacial Regeneration - Jangale Mayuri Navnath; S. D. Mankar (Emerging Trends in Personalized Medicines, 2025)
One of the most talked-about topics of the 21st century is gene therapy, which holds the promise of treating many diseases. Current gene therapy research explores a wide range of potential treatments, such as enhancing the body’s immune response to tumors, promoting the formation of new blood vessels in the heart to mitigate heart attacks, and preventing HIV replication in AIDS patients. Gene therapy involves the introduction, alteration, or replacement of genetic material within a patient’s cells to treat or prevent disease. This innovative approach has evolved significantly over the years, overcoming early challenges related to gene delivery, immune responses, and ethical considerations. Advances in viral and non-viral vector systems have improved the efficiency and safety of gene transfer, making it possible to target specific diseases more effectively. Materials and Methods: Relevant articles were thoroughly analyzed and reviewed to assess the historical, current, and future perspectives of gene therapy. Various clinical trials and experimental studies have provided valuable insights into gene-editing techniques, including CRISPR-Cas9, zinc finger nucleases, and RNA interference, all of which have expanded the therapeutic possibilities of gene-based treatments. Unlike traditional gene replacement therapy, craniofacial regeneration aims to utilize genetic vectors as supplementary elements for tissue growth and repair. The combination of viral gene therapy with craniofacial tissue engineering presents a powerful synergy that can greatly improve our capacity to repair and regenerate tissues directly within the body.
Keywords: Gene therapy; genetic disease; methods of gene therapy; perspective; viral and non-viral vectors